Relapsing-Remitting Multiple Sclerosis Is Associated With Regional Brain Activity Deficits in Motor- and Cognitive-Related Brain Areas - Du, Xiao-Feng; Liu, Jiao; Hua, Qi-Feng; Wu, Yi-Jiao (Frontiers in Neurology, 2019)
Objective: To identify the abnormal regional spontaneous brain activity associated with relapsing-remitting multiple sclerosis (RRMS), using fractional amplitude of low-frequency fluctuation (fALFF) analysis, and their relationships with clinical features. Methods: A total of twenty-six RRMS (11 males, 15 females; age, 36.58±10.82 years) and 27 status-matched healthy group (HGs; 12 males, 15 females; age, 35.85±12.05 years) underwent an Expanded Disability Status Scale (EDSS) examination. fALFF was applied to evaluate the abnormal regional brain activity associated with RRMS. Pearson’s correlation analysis was applied to calculate the correlations between the signal values of brain areas that exhibited abnormal fALFF values and clinical features. Receiver operating characteristic (ROC) curve was performed to evaluate the sensitivity and specificity of those altered brain areas to distinguish between RRMS and HGs. Results: Compared with HGs, RRMS exhibited higher fALFF in the right cerebellum posterior lobe, left orbitofrontal cortex, left dorsolateral prefrontal cortex, bilateral supplementary motor area and right fusiform gyrus, and lower fALFF values in the left hippocampus and right precuneus. ROC revealed that these areas showed two good and five fair AUC values (0.77 ± 0.03, 0.729~0.822). However, four combinations with more than five brain regions received the same best discriminatory power with sensitivity of 96.3% and specificity of 88.5%. EDSS revealed a negative correlation with supplementary motor area (r = -0.395, p = 0.046). Conclusions: RRMS is associated with abnormal regional brain activity deficits of motor- and cognitive-related areas. The fALFF parameter may serve as a potential biological marker to discriminate between the two groups.